Classification and Management of iatrogenic bile duct injury (Journal of Surgical Sciences, 2020)
The laparoscopic cholecystectomy is considered the gold standard for the treatment of benign gall bladder disease, which is associated with an increased incidence of biliary injuries. These types of injuries are multicausal, and anatomical variations or anatomical perception errors are the most common risk factors. Iatrogenic bile duct injuries are complex alterations and constitute one of the most serious complications of a cholecystectomy and require a comprehensive approach, proper drainage and timely referral to adequate treatment to improve long-term prognosis. Reconstruction and treatment techniques have been evolving. The selection of adequate treatment will impact on the patient, s quality of life.Journal of Surgical Sciences (2017) Vol. 21 (2): 110-114